Development of a mobile application for the mental wellbeing of youths (B) - Boey, Raymond Zhi Jie (Nanyang Technological University, 2020)
Mental illness is becoming a prevalent problem in Singapore as well as on the global scale. Additionally, there is an increasing number of young adults who have developed symptoms of mental illness. It is of the utmost importance to tackle this problem. Therefore, to help with this problem, a mobile application is developed that is targeted at youths to elevate their mood as well as a stepping-stone for them to be more open when seeking professional help if needed. It will encourage them to be more vocal when expressing their thoughts and at the same time have fun through the concept of gamification. In this report, the focus will be on the pet game development aspect in Unity3D. The mobile application was developed on Android Studios while the game was created on Unity3D. The programming language used for Android Studios and Unity3D were Java and C# respectively